ChemInform Abstract: Filicinic Acid Based Meroterpenoids with anti‐Epstein—Barr Virus Activities from Hypericum japonicum. Issue 38 (September 2016) - Hu, Linzhen; Zhang, Yu; Zhu, Hucheng; Liu, Junjun; Li, Hua; Li, Xiao‐Nian; Sun, Weiguang; Zeng, Junfen; Xue, Yongbo; Zhang, Yonghui
Abstract: Hyperjaponols A‐G, which possess hybrid structures of acylfilicinic acid moieties and diverse sesquiterpenoid motifs bearing unusual 6/6/11, 6/6/7/5, and 6/6/10 ring systems, are isolated from H.